War and (post)human nature: A critical posthumanist approach in obsoleting wars - Mariñas, Bennjohn Aceli B. (Animo Repository, 2025)
I will examine whether or not we can eradicate wars within this post-human world. Wars are generally understood as a state of organized and open-ended conflicts that are done through various means and different ends. Present-day theories in the philosophy of war are depicted as being deeply rooted in scientific-anthropocentric notions of “human nature”. This phenomenon is understood to be deeply embedded in the biological (or inherent) capacity of humans to commit acts of violence. This paper will examine why this deterministic and anthropocentric theorizing of wars is detrimental in theorizing for obsolescence. Posthumanism teaches us that our notions regarding “human nature” are critical in our analysis of human actions, specifically on why we do them. It is a worldview where the value of human life is decentralized and put on the same level as other life forms. To be a posthuman, therefore, is to be equally as valuable as any other form of life within the world, and to co-evolve with them in the process. I will attempt to explain why a posthuman war-free world is still feasible. As such, I claim that wars can be made obsolete through posthumanism because human beings are no longer the center of life, and have moved past attaching the phenomenon to a ‘nature’.